Prevalence of pain-related single nucleotide polymorphisms in patients of African origin with sickle cell disease. (November 2015) - Jhun, Ellie H; Yao, Yingwei; He, Ying; Mack, A Kyle; Wilkie, Diana J; Molokie, Robert E; Wang, Zaijie Jim
Background: Prospective pain genetics research is hindered by a lack of data on the prevalence of polymorphisms in pain-relevant genes for patients with sickle cell disease (SCD). For African–Americans in general, limited information is available in public databases.Methods: We prioritized and examined the genotype and allele frequencies of 115 SNPs from 49 candidate pain genes in 199 adult African–Americans and pediatric patients of African origin with SCD. Analyses were performed and compared with available data from public databases.Results: Genotype and allele frequencies of a number of SNPs were found to be different between our cohort and those from the databases and between adult and pediatric subjects.Conclusion: As pain therapy is inadequate in a significant percentage of patients with SCD, candidate pain genetic studies may aid in designing precision pain medicine. We provide prevalence data as a reference for prospective genetic studies in this population.